Hierarchical structured and programmed vehicles deliver drugs locally to inflamed sites of intestine - Li W.; Li Y.; Liu Z.; Kerdsakundee N.; Zhang M.; Zhang F.; Liu X.; Bauleth-Ramos T.; Lian W.; Mäkilä E.; Kemell M.; Ding Y.; et al. (Elsevier Ltd, 2022)
Orally administrable drug delivery vehicles are developed to manage incurable inflammatory bowel disease (IBD), however, their therapeutic outcomes are compromised by the side effects of systemic drug exposure. Herein, we use hyaluronic acid functionalized porous silicon nanoparticle to bridge enzyme-responsive hydrogel and pH-responsive polymer, generating a hierarchical structured (nano-in-nano-in-micro) vehicle with programmed properties to fully and sequentially overcome the multiple obstacles for efficiently delivering drugs locally to inflamed sites of intestine. After oral administration, the pH-responsive matrix protects the embedded hybrid nanoparticles containing drug loaded hydrogels against the spatially variable physiological environments of the gastrointestinal tract until they reach the inflamed sites of intestine, preventing premature drug release. The negatively charged hybrid nanoparticles selectively target the inflamed sites of intestine, and gradually release drug in response to the microenvironment of inflamed intestine. Overall, the developed hierarchical structured and programmed vehicles load, protect, transport and release drugs locally to inflamed sites of intestine, contributing to superior therapeutic outcomes. Such strategy could also inspire the development of numerous hierarchical structured vehicles by other porous nanoparticles and stimuli-responsive materials for the local delivery of various drugs to treat plenty of inflammatory gastrointestinal diseases, including IBD, gastrointestinal cancers and viral infections.